Four Walls Around You - National Paint, Varnish (Pamphlets corresponding to radio shows produced by the National Paint, Varnish and Lacquer Association, 1940)
Booklet corresponding to a radio broadcast program created by the National Paint, Varnish, and Lacquer Association. The booklet discusses various methods to decorate one's walls. These methods include stippling, scumbling, murals, plastics, pasterettes, and stenciling. Describes each technique and where it is most effectively employed. Includes small stylized illustrations throughout and decorated covers. The National Paint, Oil and Varnish Association, Inc. was formed in 1933 and was the national professional association representing all branches of the paint, oil, and varnish industries.
Keywords: Stencil work; Paint materials; Interior decoration; Mural painting and decoration; Varnish and varnishing; Varnish industry; Paint industry and trade; Advertising--Paint